(untitled) (Applied Biological Research, 2023)
The medicinal herb Anisomeles heyneana Benth is endemic to peninsular India. In current study the phytoconstituents in the leaves of Anisomeles heyneana were investigated. The plant material was collected from the Western Ghats in India. The phytochemicals were extracted from the leaves by preparing a methanol extract and analyzed using GC-MS and SEM-EDX. The GC-MS analysis of extract revealed the presence of 22 compounds in it. These compounds included phenolics, flavonoids, coumarins, glycosides, fatty acids, terpene and steroids. The predominant compounds in the leaves were 13, 27-cycloursan-3-one (100%), γ-sitosterol (82.04%) and n-hexadecanoic acid (34.08%). An energy-dispersive X-ray spectrometer (EDS) was employed to analyse the mass percentage of trace elements. Scanning electron microscopy showed the presence of carbon, oxygen, sodium, magnesium, aluminium, silicon, phosphorus, chlorine, calcium, magnesium, and iron. The carbon was the highest component (48.76 %) as compared with other minerals.